Dehumanization and self-alienation between culture of consumerism and global risks of postmodern age - Jašović Boris (Sociologija, 2005)
In this article possible courses of revitalization and application of concept of alienation in contemporary postmodern age would be represented. Accent would bet on two basic aspects of this phenomenon: dehumanization as alienation of human from human and self-alienation as alienation of human from it’s authentic self. We will try to perceive mentioned aspects of alienation from perspective of global paradigmatic changes which have overtaken, above all, western capitalistic societies from the middle of 70’s of XX century. We will also try to treat alienation, which presents result of negative influence of society on individual, as cultural determinant which reflects itself trough positions of modern individual within various social models: culture of consumerism and global risks; satisfaction and tremble; insecure working positions and way of constructing identity… We will point to fact that dehumanization, as result of effect of logic of capital leads to violation of humanistic relations among people, as well as self-alienation, as result of fragmentation of individual’s identity leads to depolitization of humans, which influences on violation of fundamental principles of democracy.